2019
DOI: 10.1101/671750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into Membrane Protein-Lipid Interactions from Free Energy Calculations

Abstract: Integral membrane proteins are regulated by specific interactions with lipids from the surrounding bilayer.The structures of protein-lipid complexes can be determined through a combination of experimental and computational approaches, but the energetic basis of these interactions is difficult to resolve. Molecular dynamic simulations provide the primary computational technique to estimate the free energies of these interactions. We demonstrate that the energetics of protein-lipid interactions may be reliably a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 71 publications
3
39
0
Order By: Relevance
“…Our recent study showed how the method could be extended to a CG protocol (CG-FEP) to assess relative protein-lipid binding free energies. This approach was in strong agreement with other free energy calculation methods such as potential of mean force calculation (PMF) and well-tempered metadynamics (WTMetaD) 6 .…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our recent study showed how the method could be extended to a CG protocol (CG-FEP) to assess relative protein-lipid binding free energies. This approach was in strong agreement with other free energy calculation methods such as potential of mean force calculation (PMF) and well-tempered metadynamics (WTMetaD) 6 .…”
Section: Introductionsupporting
confidence: 75%
“…Kir channels form an attractive target for applying a computational approach to compare binding affinity between phosphoinositides and also assess the impact of mutations on binding. Coarse-grained (CG) molecular dynamics (MD) simulations have previously been used to identify lipid-binding sites on ion channels [3][4][5] , as well as predicting the affinity of interactions 6 . For many years, the application of atomistic free energy perturbation (FEP) methods have been successfully applied to determine small molecule, lipid, and drug binding affinities 19 as well as to study the impact of amino acid side chain mutations 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FEP calculations were performed as described in ref. 46. In brief, a pose of Kir2.2 with PIP 2 bound at both sites 1 and 2 was extracted from the equilibrium data, and the protein and PIP 2 molecules were built into a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine bilayer using the insane protocol (64).…”
Section: Methodsmentioning
confidence: 99%
“…Further, by calculating the residence times of each interaction site, we identify their kinetic profiles, while free energy perturbation calculations (see, e.g., ref. 46) quantify the preference for PIP 2 vs. PS binding at each site. These analyses allow us to build up a picture of diverse lipid interactions on the surface of Kir2.2 channels, corresponding to the multimodal regulation of this channel by different lipid species.…”
Section: Significancementioning
confidence: 99%